(untitled) (Desenvolvimento em Questão, 2025)
The mineral extractive industry has played a central role in the economic dynamics of the Eastern Brazilian Amazon since the 1940s, especially in the state of Pará. However, there is evidence of an apparent contradiction between socioeconomic development and mining, which may deepen in the context of an energy transition in response to climate change. On one hand, large-scale projects have generated economic growth, particularly due to increases in Gross Domestic Product; on the other hand, no significant improvement in overall population well-being has been observed. In this regard, this study aims to contribute to the debate on development in Brazilian mining municipalities by analyzing the social and economic development of six mining municipalities in Pará, based on a historical approach and on the analysis of the Municipal Human Development Index and the Social Vulnerability Index using data from the 2000 and 2010 censuses. The main findings reveal that despite the economic growth during the period, most mining municipalities still exhibit high social vulnerability, even with improvements in the human development index.